Stakeholder Pressures as Determinants of CSR Strategic Choice: Why do Firms Choose Symbolic Versus Substantive Self-Regulatory Codes of Conduct? - Perez-Batres, Luis A. (Journal of business ethics, 2012)
To encourage corporations to contribute positively to the environment in which they operate, voluntary self-regulatory codes (SRC) have been enacted and refined over the past 15 years. Two of the most prominent are the United Nations Global Compact and the Global Reporting Initiative. In this paper, we explore the impact of different stakeholders’ pressures on the selection of strategic choices to join SRCs. Our results show that corporations react differently to different sets of stakeholder pressures and that the SRC selection depends on the type and intensiveness of the stakeholder pressures as well as the resources at hand to respond to those pressures. Our contribution offers a more specific and finely variegated analysis of firm-stakeholder interactions.